Investigation on zinc oxide coated carbon nanotube : flexible piezoelectric generator - Tay, Hsing Yen. (2013)
With the urgent needs of "green" energy resource, researchers and scientists have been trying to covert waste energy like noise, body movements or even music from the environment into electricity using piezoelectric generators. These generators can be used in small devices to make them portable, wireless and self sustainable.